Answer:
f(x+2) = 3(x+2)^2 + 2(x+2 + 1
Step-by-step explanation:
you need to replace the x with x+2

The unknown b is stuck in the exponent position.
We can can fix that by using logarithms.
Log is the inverse operation of the exponential.
We'll take log of each side.
Log of what base tho?
Well, the base of our exponential is e,
so we'll take log base e of each side.

We'll apply one of our log rules next:

This allows us to take the exponent out of the log,

Another thing to remember about logs:
When the base of the log matches the inside of the log,
then the whole thing is simply 1,



So our equation simplifies to this,

As a final step, divide both sides by 3,

k, hope that helps!
Answer:
11 nickels, 15 dimes, 22 quarters
Step-by-step explanation:
number of nickels = x
number of dimes = x+4
number of quarters = 2x
- - - - - -
total of nickels = 5x cents
total of dimes = 10x + 40 cents
total of quarters = 50x cents
- - - - - -
755 = 5x + 10x + 40 + 50x
755 = 65x + 40
715 = 65x
x = 11
x+4 = 15
2x = 22